UPAYA MENUMBUHKEMBANGKAN OLAHRAGA TRADISIONAL EGRANG PADA ANAK DI DESA RAGEMANUNGGAL KECAMATAN SETU - Mukhozin, Tri; Kusumawati, Mia; Iskandar, Tatang (Universitas Islam 45 Bekasi, 2025)
Traditional sports are the result of the creativity, expression, and values of society that have been passed down through generations as part of cultural heritage. One of the traditional sports still recognized in Indonesia is egrang, a game that emphasizes concentration, balance, agility, and physical endurance to cover a predetermined distance. Each step in the game requires players to maintain their balance in order to move forward without falling, and then return to the starting point to earn points. The educational values embedded in egrang make it not only a recreational activity but also a medium for character building, especially among children. However, with the rapid development of modern lifestyles, young people’s interest in traditional sports has significantly declined, creating an urgent need for revitalization efforts to ensure their preservation. This community service program was implemented in Ragemanunggal Village, Setu Subdistrict, as an effort to promote and revitalize the traditional sport of egrang among children. The program was designed through socialization, hands-on training, and continuous mentoring to foster children’s interest and skills in playing egrang. Moreover, the active involvement of children is expected to strengthen their appreciation of local culture while cultivating sportsmanship, togetherness, and self-confidence. The results indicated strong enthusiasm from the participants as well as improvements in basic egrang playing skills. Therefore, the preservation of traditional sports can be effectively achieved through early introduction, while also contributing positively to children’s character development and the safeguarding of cultural heritage.